Strategi Menurunkan Prevalensi Gizi Kurang Pada Balita di Provinsi Jambi - Kalsum, Ummi; Jahari, Abas Basuni (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2015)
ABSTRACT Malnutrition is a major cause of morbidity and mortality among children in developing countries. This study aims to examine strategies to reduce the prevalence of malnutrition (underweight) in an effort to achieve the target of MDG's in nutrition programs in Jambi by analyzing the magnitude of the problem of nutrition according to indicators of W/A, H/A and W/H in infants (children aged 0-60 months). The data analyzed in this study came from the Health Research Association (Riskesdas) 2007 held in Jambi Province. The number of samples in the study were as 2213 of underfive children. The analysis showed that 36.6% of underfive children were stunting (H/A), 19.6% of underfive children were underweight (W/A) and 17.3% wasting (W/H). There are 80% of the City and  District have malnutrition prevalence least not yet achieved the MDG's targets ranged from 15.9 to 26.3%. The proportion of infants not stunted (normal according to the W/A) but wasted were 5.3%, varies between 3.5% - 15.8% in the District/City. The proportion of not stunted (normal) but wasted (N-K) is what can be intervened by supplementary feeding (PMT) with immediately visible results. When all N-K children can be handled, the MDG's targets can be achieved in Jambi Province (14.3%). Strategies that can be done is to revitalize primary health centers and growth monitoring at integrated health post (Posyandu). Key Words : underweight, stunted, wasted, underfive children